(untitled) (Research, Society and Development, 2022)
The insertion of long-acting reversible contraceptive methods at the time of postpartum promotes improvements in access to reproductive planing. The intrauterine device (IUD) is considered a safe, effective and reversible method. Therefore, the objective was to analyze the scientific production on the follow-up of IUD inserted in the postpartum period. This is an integrative review, accomplished on February 21, 2021, whose eligibility criteria were articles or official documents that addressed guidelines in the follow-up of the IUD inserted in the postpartum period and puerperium. After crossings using the descriptors “intrauterine device”, “PPIUD”, “Follow-up” and “postpartum/puerperium” in the portal of periodicals Capes, Scielo, Medline/Pubmed (Virtual health library). The final sample consisted of four articles. Studies have shown that side effects such as pain, bleeding, and poor positioning can occur at the first to eight weeks after IUD insertion. To assess IUD bad positioning, ultrasound and speculum examination should be performed. Follow-up consultations can be in person or by telephone, carried out by trainer primary care professionals. It is concluded that when users receive information clearly, the chances of continuity of the method are significantly higher.